Evaluation Of The Effect Of Metformin On The Level Of Some Biochemical Parameters In Patients With Type2 Diabetes Mellites (The Review of Diabetic Studies, 2025)
Introduction: Diabetes mellitus (DM) is a significant health disorder impacting individuals globally, characterized by a high prevalence rate.  Diabetes mellitus (DM) is categorized by its etiology into type 1 diabetes mellitus (T1DM) and type 2 diabetes mellitus (T2DM); several risk factors, including age, genetic predisposition, and obesity, contribute to the onset of T2DM.  Metformin is an established first-line pharmacotherapy for individuals with type 2 diabetes mellitus, aimed at enhancing glycemic control. Material and Methods: This cross-sectional study examined 89 diabetes patients from September 2024 to June 2025, dividing them into two groups: a control group of 36 healthy individuals and a T2DM group of 53 patients on metformin therapy. A pre-structured questionnaire was created to gather patient records, including age, gender, BMI, and metformin dosage. Serum parameter levels were evaluated to compare with the control group, assessing reduction or borderline values. Result: The study compared 53 type 2 diabetes patients and 36 control subjects, finding that females were more frequent in both groups. Age and body mass index showed no significant difference between the groups. Generally, the biochemical parameters in patients and controls show significant differences in ferritin, vitamin B12 levels, HbA1c, and adenosine triphosphate (ATP) levels. While RBC, Hb, GIF, and LA levels revealed that there is no significant difference between groups. Metformin (1000 mg)-induced biochemical parameter analysis revealed significant differences in ferritin, vitamin B12, HbA1c, and ATPS between control and T2DM patients, while non-significant differences were observed in RBC, Hb, GIF, and LA. On the other hand, ATPS, RBC, GIF, LA, and vitamin B12 levels showed significant differences between control and T2DM patients by using 2000 mg of metformin per day, while RBC, Hb, GIF, and LA showed non-significant differences between the groups. Conclusion: The biochemical parameters showed significant differences in ferritin, vitamin B12, HbA1c, and ATP levels, but no significant differences in RBC, Hb, GIF, and LA levels. Metformin-induced biochemical parameters showed significant differences in ferritin, vitamin B12, HbA1c, and ATPS.